PTU-154 Investigation of the optimal duration of the glucose hydrogen methane breath test. (28th May 2012) - Grace, E; Thomas, K; Gupta, S; Lalji, A; Whelan, K; Shaw, C; Andreyev, J
Abstract : Introduction: Historically, the glucose hydrogen breath test has been popular for diagnosing small intestinal bacterial overgrowth (SIBO). Lately the glucose hydrogen methane breath test has become available. It is non-invasive and simple to carry out. This test is used as a part of standard clinical practice in patients suspected of having SIBO in our hospital. There are limited published data on the optimal test duration, with 3 h being the longest reported. This study aimed to determine if there is a significant difference in the number of patients who would be considered positive for SIBO depending on test duration. Methods: Patients in whom the gastroenterologist suspected SIBO underwent a breath test performed by endoscopy nurses using the QuinTron BreathTracker DP Digitial Microlyzer that measures hydrogen (H2 ) and methane (CH4 ) concentrations in parts per million (ppm). Pre-test preparation included avoiding slowly absorbed carbohydrates, fibre and large meals and limiting dairy intake and carbonated drinks for 24 h, a 12 h fast and avoiding exercise and cigarette smoking for 2 h. Breath H2 and CH4 concentrations were noted at baseline. Subjects then consumed 75 g (or 50 g if weight was <50 kg) in 100 ml of water. Thereafter, breath H2 and CH4 values were recorded every 20 min for 3 h (or less if positive). Positive test was defined as fasting H2 ≥20 or CH4 ≥10 ppm or a rise in H2 ≥12 or CH4 ≥6 ppm. Results: 98 males and 95 females, median age 63 years (range 28–86) underwent a breath test. Of these, 67 (35%) had a positive result for one or both gases: 18 (32%) at baseline, 39 (60%) by 40 min, 56 (84%) by 100 min, 60 (90%) by 140 min, 67 (100%) by 160 min. 126 patients had negative breath tests; n=75 had the test performed for a full 3 h, 26 (20%) had the test performed for 100 min only. In patients where the test was performed for 3 h the 95% CI for a false negative result at 100 min is 0.003 to 0.10. Conclusion: Most patients with SIBO will have a positive result by 100 min. This suggests that a reduction in the duration of the test can be achieved without compromising the number of true positives being diagnosed with SIBO. Competing interests: None declared.